Synthesis of Amino Chalcones in Presence of Ionic Liquid as Soluble Support - Pan, Xianhua; Yi, Fengping; Zhang, Xuan; Chen, Shihong (Asian Journal of Chemistry, 2012)
A microwave-assisted liquid phase synthesis of aminochalcones was developed by using aldehyde-functionalized ionic liquid as soluble support. Ionic liquid bound aminoacetophenone was treated with aromatic aldehyde to give supported chalcone derivatives. After cleavage, the target compounds were obtained in 83-92 % yields and ³ 95 % purities without column chromatographic purification. The recovered aldehyde-functionalized ionic liquid could be reused for several times without affecting its activity and the yields of desired compounds were between 86-89 %. These results indicated that the presented method could be applied efficiently to the liquid phase combinatorial chemistry based on aldol condensation.